1977
DOI: 10.1002/j.2050-0416.1977.tb06806.x
|View full text |Cite
|
Sign up to set email alerts
|

Chelators and Metal Buffering in Fermentation

Abstract: Trace elements are important components of brewer's wort. The effect of these metals is dependent upon the metal binders, (chelators) present. These chelators are wort components with reactive groups such as carboxyl, sulphydryl, o-diphenol or amine. The properties of different types of complex are briefly reviewed together with the general equations for their stability. The stability of some of the complexes formed in wort is comparable with the stability of EDTA com plexes.The distribution of metals can be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Thus, to estimate the real amount of ions removed from the wort, both the mass of spent grains and their concentration of Mg 2+ were taken into account. In the presented work, the nitrogen compounds and polyphenols in the raw materials and wort were not determined, but for future research it is suggested that there should be a focus on these compounds as well, owing to their chelating properties (32). Generally, wheat contains more proteins than barley (15), and barley malt proteolytic enzymes solubilize and partially degrade wheat proteins (33).…”
Section: Magnesium Ionsmentioning
confidence: 99%
“…Thus, to estimate the real amount of ions removed from the wort, both the mass of spent grains and their concentration of Mg 2+ were taken into account. In the presented work, the nitrogen compounds and polyphenols in the raw materials and wort were not determined, but for future research it is suggested that there should be a focus on these compounds as well, owing to their chelating properties (32). Generally, wheat contains more proteins than barley (15), and barley malt proteolytic enzymes solubilize and partially degrade wheat proteins (33).…”
Section: Magnesium Ionsmentioning
confidence: 99%
“…Industrial feedstocks contain a multitude of soluble chelating and insoluble adsorbing materials that act as sinks to reduce the bioavailability of metal ions (Jones and Greenfield, 1984). This has been addressed for brewing fermentations by Jacobsen et al (1977). Because of the difficulties in differentiating between free and bound metal ion concentrations in complex media, optimization of "available" Mg2+ levels in fermentations would be problematic but, nevertheless, worthwhile.…”
mentioning
confidence: 99%